[2](1, 3)Adamantano[2](2, 7)pyrenophane: A Hydrocarbon with a Large Dipole Moment. (1st July 2016) - Kahl, Paul; Wagner, J. Philipp; Balestrieri, Ciro; Becker, Jonathan; Hausmann, Heike; Bodwell, Graham J.; Schreiner, Peter R.
Abstract: The fusion of the sp 3 ‐hybridized parent diamondoid adamantane with the sp 2 ‐hybridized pyrene results in a hybrid structure with a very large dipole moment which arises from bending the pyrene moiety. Presented herein is the synthesis, study of the electronic and optical properties, as well as the dynamic behavior of this new hydrocarbon.